Sex‐dependent correlates of arterial stiffness in Tanzanian adults. Issue 11 (14th September 2021) - Karand, Julie C.; Reis, Karl; Stephano, Ponsiano F.; Gargurevich, Nick; Zhou, Joanne; Desderius, Bernard; Fadhil, Salama; Ladha, Yumna; Rosengard, Rachel; Kowal, Daniel R.; Peck, Robert N.
Abstract: Objective: Arterial stiffness is a known indicator for cardiovascular disease. However, the factors that lead to arterial stiffening have primarily been studied in participants from high‐income countries. Here, we examine clinical and lifestyle metrics in relation to arterial stiffness in Tanzanian adults. Methods: We performed pulse wave velocity (PWV), the gold standard measure of arterial stiffness, on 808 Tanzanian adults (ages 18–65) enrolled in a longitudinal cohort studying trends in blood pressure. Results: As expected, PWV was strongly associated with age, blood pressure and sex. We controlled for these factors in our statistical analysis. Lifestyle metrics were compared across multiple PWV quantiles. We found that determinants of PWV varied by sex: in female participants, PWV was associated with common obesity metrics and menopause, while in male participants, PWV was associated with HIV status and duration of anti‐retroviral therapy (ART). Further clinical and lifestyle factors such as marriage status and type of occupation were also significantly associated with PWV and moderated by sex. Conclusion: Together, our data demonstrate the importance of studying sex‐specific causal pathways for arterial stiffness and of including under‐represented populations in these studies.